Private Sector Development in an Emerging World: Inclusive Policies and Strategies for the Formal and Informal Economy - Diederik Boer; Harald Sander; Katharina Friz; Antonella Anastasi (De Gruyter, 2024)
This book explores the interactions between private sector development, public policies and societal institutions with a strong view on contributing to sustainable and inclusive development in emerging countries. The private sector is often praised as an engine of economic growth. This belief has led to significant efforts to promote private sector development in emerging countries. Development agencies prioritize private sector development and national governments are following suit, resulting in often huge incentives to stimulate and attract private investment. However, private sector development is not a panacea for sustainable and inclusive development as the past decades have clearly shown. Economic growth, societal development and environmental sustainability are often in a sharp conflict; and more often than not economic growth has failed to improve the lives of all citizens. This book examines the role the state and the private sector should play to benefit from the dynamics of business development, while ensuring that these benefits are shared broadly without jeopardizing sustainability. The views presented differ in detail, but the analyses and case studies presented share common themes, namely that the relative roles of state and private sector of should be balanced and that this particular balance should be based on the context of each country in order to make the private-public sector interaction work for all people. ; This book explores the interactions between private sector development, public policies and societal institutions with a strong view on contributing to sustainable and inclusive development in emerging countries. The private sector is often praised as an engine of economic growth. This belief has led to significant efforts to promote private sector development in emerging countries. Development agencies prioritize private sector development and national governments are following suit, resulting in often huge incentives to stimulate and attract private investment. However, private sector development is not a panacea for sustainable and inclusive development as the past decades have clearly shown. Economic growth, societal development and environmental sustainability are often in a sharp conflict; and more often than not economic growth has failed to improve the lives of all citizens. This book examines the role the state and the private sector should play to benefit from the dynamics of business development, while ensuring that these benefits are shared broadly without jeopardizing sustainability. The views presented differ in detail, but the analyses and case studies presented share common themes, namely that the relative roles of state and private sector of should be balanced and that this particular balance should be based on the context of each country in order to make the private-public sector interaction work for all people.
Keywords: 330; Privatsektor; Schwellenländer; Nachhaltiges Wachstum; Entwicklungskonzept; Private Sector Development; Industrial Policy; Innovation; Inclusive Growth; Sustainability; Political Economy